The emerging role of advanced neuroimaging techniques for brain metastases - Nowosielski, Martha; Radbruch, Alexander (Chinese clinical oncology, 2015)
Brain metastases are an increasingly encountered and frightening manifestation of systemic cancer. More effective therapeutic strategies for the primary tumor are resulting in longer patient survival on the one hand while on the other, better brain tumor detection has resulted from increased availability and development of more precise brain imaging methods. This review focuses on the emerging role of functional neuroimaging techniques; magnetic resonance imaging (MRI) as well as positron emission tomography (PET), in establishing diagnosis, for monitoring treatment response with an emphasis on new targeted as well as immunomodulatory therapies and for predicting prognosis in patients with brain metastases.